Proximal hamstring strains of stretching type in different sports - Askling, C. M.; Tengvar, M.; Saartok, T.; Thorstensson, A. (The American Journal of Sports Medicine, 2008)
Hamstring strains can be of at least 2 types, 1 occurring during high-speed running and the other during motions in which the hamstring muscles reach extreme lengths, as documented for sprinters and dancers.